Role of cell membrane integrity and oxidation stress in development of external browning of white seedless table grapes (Vitis vinifera L.) - Botes, Wilhelmina Jacoba (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhDAgric)--Stellenbosch University, 2023.